Raw materials partner Chile: More than just a supplier. How the EU should strengthen strategic raw material partnerships and leverage geopolitical dynamics - Inga Carry (Stiftung Wissenschaft und Politik (SWP), 2025)
In summer 2023, the EU entered a strategic raw materials partnership with Chile. While the EU is seeking to gain better access to critical raw materials such as lithium and copper, Chile is aiming to diversify its raw materials sector and boost local value creation. Despite progress having been made in the scientific and technological spheres, industrial cooperation has so far fallen short of expectations. To fully realise the potential of the partnership, the EU should seek to ensure that its existing initiatives with Chile are more closely aligned and should make more effective use of synergies between raw materials, renewable energy and hydrogen. This will require stronger investment incentives for European companies. Given the new US trade policy, it is especially important that the EU underpins its partnership promises through concrete actions in order to demonstrate that it is a reliable partner.
Keywords: 320; raw materials; Chile; EU; geopolitical dynamics; lithium; copper; industrial cooperation; partnership; renewable energy; hydrogen; mining companies; CODELCO